Validating the Immigration Policies in Comparison (IMPIC) dataset - Samuel D. Schmid; Marc Helbling (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2016)
The aim of this paper is to discuss the external and internal validity of the newly created Immigration Policies in Comparison (IMPIC) dataset. After presenting its theoretical conceptualization, we compare the IMPIC to other datasets in this policy field. Next, using a variant of principal component analysis, we empirically analyze its sub-dimensions. Among other things, and contrary to some expectations in the extant literature, we find that there appears to be a comprehensive and consistent dimension comprising immigration policies for the fields of labor migration, family reunification, and asylum seekers. We also offer two typologies, which can be used to map the most important dimensions of variation. These validity tests allow us to better understand what the IMPIC dataset measures, what its main dimensions are, and how it can be compared to other indices that measure immigration policies.
Keywords: 300; immigration policy; open borders; internal validity; external validity; principal component analysis; index-building